AFP and CA-125 as an accurate risk factor to predict eye metastasis in hypertension patients with liver carcinoma: A STROBE-compliant article - Tang, Jing; Zhang, Li-Juan; Kang, Min; Huang, Rong; Shu, Hui-Ye; Wei, Hong; Zou, Jie; Pan, Yi-Cong; Ling, Qian; Shao, Yi (Frontiers in Genetics, 2022)
PURPOSE: Primary liver carcinoma is a common malignant tumor. In this study, we analyzed the differences between hypertension patients with ocular metastasis of liver cancer and those with metastases to other sites, the correlation between history of HBV and liver cancer metastasis, and independent risk factors for ocular metastasis. METHODS: We used treatment records from 488 patients with metastases of primary liver cancer from August 2001 to May 2015, divided into two groups based on metastatic sites: OM (ocular metastasis) and NOM (non-ocular, other sites of metastasis) groups. The Student’s t-test and Chi-square test were used to assess the significance of differences between the groups and define the relationship between history of HBV and ocular metastasis of liver cancer. Binary logistic regression analysis was used to identify indicators of ocular metastasis of liver cancer and receiver operating curve (ROC) analyses to estimate their diagnostic value. RESULTS: No significant differences in sex, age, tumor stage, pathological type, or treatment were identified between the OM and NOM groups, while the prevalence of HBV was higher in the former than that in latter, confirming the association between history of HBV and ocular metastasis. Binary logistic regression demonstrated that AFP and CA-125 were independent indicators of liver metastasis (both P < 0.001). ROC curve analyses generated cut-off values for AFP and CA-125 of 957.2 ng/ml and 114.25 U/ml, respectively, with corresponding AUC values of 0.739 and 0.810. The specificity of the combination of AFP and CA-125 was higher than either factor separately.